Alterations in the prevalence and serotypes of Streptococcus pneumoniae in elderly patients with community-acquired pneumonia: a meta-analysis and systematic review - Xinyue Luo; Qianli Yuan; Jing Li; Jiang Wu; Binghua Zhu; Min Lv (Pneumonia)
Abstract Background Pneumococcal pneumonia is a common disease with a significant impact on morbidity and mortality among the elderly population. The main purpose of this meta-analysis was to estimate the prevalence of community-acquired pneumonia (CAP) in elderly individuals caused by Streptococcus pneumoniae (S. pneumoniae). Methods A systematic search of the PubMed, Web of Science, and Scopus databases was conducted for relevant studies published between January 2013 and December 2023. Subgroup analysis and meta-regression were used to identify the sources of heterogeneity affecting the 87,430 patient studies obtained from 47 papers that met the inclusion and exclusion criteria. Results The combined prevalence rate for S. pneumoniae among all CAP patients included in the study was 14.8% (95% confidence interval [CI]: 12.3–17.8%). The 5-year pooled prevalence decreased from 16.5% (95% CI: 15.0–18.2%) in 1996–2000 to 8.4% (95% CI: 6.3–11.0%) in 2016–2020 for bacterial culture alone and from 17.4% (95% CI: 16.3–18.7%) to 13.5% (95% CI: 10.7–16.8%) for bacterial culture and urinary antigen testing (UAT) combined (P < 0.001). The most prevalent serotype was serotype 3, followed by serotypes 8, 19 A, 22 F, 11 A, 5, 9 N, 12 F, 6 A, and 10 A. The vaccine-serotype coverage was 53.5% for PCV 13, 60.5% for PCV 15, 85.2% for PCV 20 and 88.6% for PPSV 23. Conclusion These findings indicate a decrease in the overall burden of pneumococcal CAP among elderly individuals over the decade, which lends support to the proposition that the delivery of immunization should be expanded across the life course.